Syntactic Analysis of Imperative Sentence in Jambi Malay Language Jangkat Isolect - Nurmisliah Nurmisliah; Dodi Oktariza; Asridayani Asridayani (Krinok:Jurnal Linguistik Budaya, 2017)
The purposes of this research are: (1) to explain the types of imperative sentence in Jangkat Isolect especiallyDanau Pauh village. (2) to describe the function of imperative sentence in Jangkat Isolect community; and (3) toexplain the structure of sentences (syntax) of imperative sentences that found in Jangkat Isolect. This research usesdescriptive qualitative method. A source of data in this research is imperative sentences in Jangkat Isolect community.This research is divided in three procedures; they are collection the data, analyzing the data, and presenting the data.In collecting the data, data are gathered by observation method and interview method. Meanwhile, the main techniquein collecting the data is eliciting technique, which is continued by several techniques, i.e. recording technique and notetechnique. The main technique in observation method is participant observational method which is continued byadvanced note technique. In analyzing the data, the research is done by using distributional method, translationalmethod, and referential method. The results of the analysis are provided by formal and informal methods.Keywords: Imperative, Sentence, Syntax, Isolect, Jangkat, Danau Pauh.